Education for cosmopolitan citizenship: A framework for language learning - Osler, Audrey; Starkey, Hugh (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Education for citizenship and the promotion of language learning for intercultural communication are both responses to globalisation. This article introduces an approach to citizenship education we call education for cosmopolitan citizenship which is explicitly linked to human rights principles and standards. Rather than focussing on differences and cultural barriers to be overcome, education for cosmopolitan citizenship starts from our common humanity. Teachers are professionals who should ground their actions and judgements in the normative standards of human rights law such as the United Nations Convention on the Rights of the Child (CRC). This provides a language for identifying and naming injustices and discriminations and enables dialogue across difference. Rather than having a primary sense of belonging focused on membership of a nation-state, education for cosmopolitan citizenship accepts that learners celebrate multiple identities and loyalties. The article concludes with some practical examples of how this perspective is implemented in language classrooms.